Changes in angiogenesis and hypoxia‐inducible factor‐1α protein expression in relapsed/refractory indolent non‐Hodgkin lymphomas. (13th September 2013) - Minoia, Carla; Quero, Carmela; Asselti, Mariaconsilia; Galise, Ida; Marzano, Alessia L.; Iacobazzi, Angela; Rana, Antonio; Merchionne, Francesca; Serratì, Simona; De Tullio, Giacoma; Quintana, Giovanni; Casiello, Michela; et al.
Summary Angiogenesis is involved in the pathogenesis and progression of non‐Hodgkin lymphomas (NHL), and hypoxia‐inducible factor‐1α (HIF‐1α, also termed HIF1A) might contribute to this process. Currently, there is no direct evidence that the clinical progression of indolent NHL is associated with angiogenesis, and the expression of HIF‐1α at recurrence is unknown. Matched lymph node biopsies at diagnosis and recurrence of relapsed/refractory indolent NHL patients were analysed by immunohistochemical and morphometric analysis. We observed an increased vascular network and HIF‐1α protein expression in the second biopsy, providing direct evidence that angiogenesis is an essential process for disease progression.